Valuing a Road Network Improvement using Stated Preferences Methods - Bengochea Morancho, Aurelia; del Saz Salazar, Salvador (European Journal of Transport and Infrastructure Research, 2003)
In this paper we address, from a double perspective, the social valuation of transport improvements caused by the construction of a new motorway. First, we estimate the value citizens confer on this infrastructure as a whole. Second, we assess the time savings and the reduction in the risk of accidents the new motorway might be expected to bring about in relation to roads used at the moment. To do this, we use two approaches based on individuals’ stated preferences: the contingent valuation method and conjoint analysis. The results show the social benefits of this project to be positive, although to what extent depends on initial assumptions. The information provided in this study will be useful to public managers since it can be incorporated in a cost-benefit analysis on the social profitability of this public investment.